2014
DOI: 10.5966/sctm.2013-0151
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal Transplantation of Adenovirus-Generated Induced Pluripotent Stem Cells for Treating Neuropathological and Functional Deficits in a Rodent Model of Huntington's Disease

Abstract: Induced pluripotent stem cells (iPSCs) show considerable promise for cell replacement therapies for Huntington's disease (HD). Our laboratory has demonstrated that tail-tip fibroblasts, reprogrammed into iPSCs via two adenoviruses, can survive and differentiate into neuronal lineages following transplantation into healthy adult rats. However, the ability of these cells to survive, differentiate, and restore function in a damaged brain is unknown. To this end, adult rats received a regimen of 3-nitropropionic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Finally, establishing this patient-derived model requires only minimal technical and financial resources, and is ideally suited for smaller laboratories. In addition, should the need arise in follow-up experiments, patient fibroblasts can be transformed into IPSCs that can be differentiated into neuronal lineages (86). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, establishing this patient-derived model requires only minimal technical and financial resources, and is ideally suited for smaller laboratories. In addition, should the need arise in follow-up experiments, patient fibroblasts can be transformed into IPSCs that can be differentiated into neuronal lineages (86). …”
Section: Discussionmentioning
confidence: 99%
“…15 Currently, iPSC research is focused on numerous diseases, especially genetic diseases such as familiar Alzheimer's disease, Huntington's disease, and Parkinson's disease. [16][17][18] In this study, we developed a simple, noninvasive, and acceptable method to generate iPSCs from renal tubular cells, thus providing an ideal cell source for iPSC generation. In contrast to other tissues sources such as skin and blood, which require a traumatic harvesting procedure, urine was easily accessible and was with minimum effort.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic differentiating iPSCs follow similar developmental principles as hESC‐derived neurons, although the neural differentiation efficiency can differ between different iPSC lines . Targeted differentiation of iPSCs toward neuronal subtypes has been achieved by various research groups, using different approaches to generate a variety of neuronal cells including medium spiny neurons, dopaminergic neurons, motor neurons, nociceptors, and pyramidal cortical neurons . Furthermore, it was shown that these neuronally differentiated cells are capable of repeated action potential firing, suggesting advanced maturation .…”
Section: Induced Pluripotent Stem Cells As a Therapy In Strokementioning
confidence: 99%